Designating Hucho taimen fishery management zones in Mongolia based on simulation of spawning dates - Zanden, M.J. Vander; Joppa, L.N.; Allen, B.C.; Chandra, S.; Gilroy, D.; Hogan, Z.; Maxted, J.T.; Zhu, J.; Joppa, Lucas (Ecological Applications, 2007)
The ecological impacts of recreational fisheries are of growing concern and pose a number of unique management challenges. Here we report on our efforts to provide guidance for managing a recreational fishery for taimen, the giant Eurasian trout (Hucho taimen) in Mongolia. This species has declined dramatically across its range of Siberia and Central Asia, and is currently listed as endangered in Mongolia. Strong populations persist in remote regions of Mongolia because of limited anthropogenic impacts and harvest, though interest in the fishery is expanding rapidly. Current fishing regulations list the spring “opening date” for taimen fishing as 15 June, although regulations have not been consistently enforced, partially because taimen spawn much earlier than 15 June in much of the country. Through a combination of statistical models, climate data, knowledge of taimen biology, and geographic information systems (GIS), we model taimen spawning dates for potential habitat in Mongolia. A parametric bootstrap procedure was used to simulate variability in spawning date derived from inter-annual climate variability and model error, from which we estimated the date in which taimen spawning is predicted to occur with 90% confidence. We recommend the designation of three fisheries management zones, with corresponding opening dates of 20 May, 1 June, and 15 June. Our fishery opening date recommendations are less restrictive than existing regulations. Provided there is little or no catch-and-release fishing mortality, this approach serves both environmental and human needs by protecting taimen during the reproductive period, while still allowing a post-spawning catch-and-release fishery that benefits local economies and generates revenue (through fishing concession fees) for local conservation efforts.